Plug&Play Fiber‐Coupled 73 kHz Single‐Photon Source Operating in the Telecom O‐Band. Issue 6 (11th May 2020) - Musiał, Anna; Żołnacz, Kinga; Srocka, Nicole; Kravets, Oleh; Große, Jan; Olszewski, Jacek; Poturaj, Krzysztof; Wójcik, Grzegorz; Mergo, Paweł; Dybka, Kamil; Dyrkacz, Mariusz; Dłubek, Michał; et al.
Abstract: A user‐friendly, fiber‐coupled, single‐photon source operating at telecom wavelengths is a key component of photonic quantum networks providing long‐haul, ultra‐secure data exchange. To take full advantage of quantum‐mechanical data protection and to maximize the transmission rate and distance, a true quantum source providing single photons on demand is highly desirable. This great challenge is tackled by developing a ready‐to‐use semiconductor quantum‐dot‐based device that launches single photons at a wavelength of 1.3 µm directly into a single‐mode optical fiber. In the proposed approach, the quantum dot is deterministically integrated into a nanophotonic structure to ensure efficient on‐chip coupling into a fiber. The whole arrangement is integrated into a 19ʺ compatible housing to enable stand‐alone operation by cooling via a compact Stirling cryocooler. The realized source delivers single photons with a multiphoton events probability as low as 0.15 and a single‐photon emission rate of up to 73 kHz into a standard telecom single‐mode fiber. Abstract : A user‐friendly, compact, and portable triggered single‐photon source operating in the telecom O‐band is demonstrated. The device provides single photons with g (2) (0) = 0.15 and a flux of up to 73 kHz at a standard physical‐contact single‐mode fiber connector output. A fully deterministic fabrication technology makes it the first application‐ready quantum‐dot‐based source to enable ultra‐secure data exchange in future fiber‐based quantum communication networks.